Use of recombinant factor VIIa in the perioperative period - Levi, M. (Hämostaseologie, 2009)
Recombinant activated factor VII (rFVIIa) is a pro-haemo -static agent that can be used for patients with haemophilia and inhibiting antibodies towards a coagulation factor. Recombinant factor VIIa is, however, increasingly used for several other indications, including patients who experience serious and life-threatening bleeding. In addition, rFVIIa has been evaluated for the prevention of major blood loss in patients undergoing surgical procedures that are known to be associated with major blood loss. In this manuscript we review the data on efficacy and safety of rFVIIa in the prevention of excessive blood loss and trans-fusion requirements in the perioperative period.We conclude that recombinant factor VIIa is a promising agent for perioperative prevention of major blood loss but that its efficacy will probably vary between specific clinical settings. Its exact place in surgery warrants further clinical trials in various situations that will also more precisely determine the safety of this intervention.
Keywords: Factor VIIa